The potential roles of engineers in knowledge management: an overview - Wong, Kuan Yew (The Institution of Engineers, Malaysia, 2005)
For ages, engineers have worked with tangible resources such as physical parts, components, subassemblies and products. However, with the advent of the knowledge economy, knowledge has become one of the most indispensable resources for viability and success. Nowadays, organisations are adopting Knowledge Management (KM) in order to convert themselves into knowledge-based enterprises. Engineers with their varied knowledge, skills and expertise can certainly be utilised to assist in the KM arena.